Custom Fabrication of a 3‐Dimensionally Printed Helmet for Improved Socialization and Subjective Self‐Assessment in a Case of Acquired Cranial Defect: A Case Presentation. Issue 6 (30th December 2017) - Colasante, Cesar; Sanford, Zachary; Castro, Nileyma; Bartels, Matthew N.
Abstract: Traumatic injury and subsequent residual cosmetic deformity are subject of intense scrutiny for their effects on objective health measures assessing patient morbidity and mortality. Although these remain principal concerns of all members of the treatment team, of less immediate yet lasting importance to the patient are the social costs of such disfigurement. Subjective feelings of unease and embarrassment can hinder social reintegration and encourage deteriorating psychosocial health. The following presents a case of one such individual who sustained traumatic brain injury and associated pneumocephalus and osteomyelitis requiring surgical debridement with bifrontal craniectomy and lobotomy. Postoperative management was cosmetically improved by the application of a custom‐fabricated, 3‐dimensionally printed helmet used in place of generic over‐the‐counter hardware, and the associated improvement reported in patient satisfaction is reported. Level of Evidence: V